Dynamic monitoring of key-performance indicators in industrial environments - Pereira, Arnaldo (2018)
Manufacturing companies generate huge amounts of relevant data that, potentially, can help the decision makers to monitor and supervise the health status of the shop-floor. Many problems are present that prevent this monitoring, namely the identification of which data should be collected, how to execute this collection or how this data should be analysed and displayed to the user. This paper deals with the last issue, where a dynamic and responsive User Interface is developed enabling the decision maker, having an in-the-mesh intervention, to constantly monitor relevant Key-Performance Indicators (KPI). The paper describes the development of such tool, considering a web-based approach under a platform agnostic perspective. The user interface presents an dynamic view over the aggregated KPI, where data is annotated with relevant warning information.